Early Detection Of The Threat Of Transfer Pricing Practices In Nickel Exports For State Revenue - Sitindaon, Novaldi; Andoko, Djoko; Rahajeng Widyarsih , A. Victoria; Ayu Permatasari, Diah (CV RIFAINSTITUT, 2025)
The urgency of transfer pricing supervision in nickel exports lies in the potential for significant loss of tax revenue due to price manipulation practices between affiliated entities. If not addressed, this will weaken fiscal resilience and hinder the financing of national strategic programs. The purpose of the study is to analyze the Early Detection of the Threat of Transfer Pricing Practices in Nickel Exports for State Revenue. The method used is SWOT AHP. The results of the study show that based on the analysis using the Analytic Hierarchy Process (AHP) method, the SO1 strategy obtained the highest score (7.736) and was prioritized as the main strategy in early detection of the threat of transfer pricing in nickel exports. This strategy emphasizes optimizing PMK 172/2023 through the integration of Automatic Exchange of Information (AEOI) and big data processing, thus enabling a more accurate preparation of corporate risk profiles based on global transactions. The SO2 strategy, which integrates e-invoicing systems with AI and machine learning to detect price and volume anomalies, occupies second priority. Meanwhile, the SO3 strategy that focuses on the use of international cooperation is in third place. The highest criteria weight fell on Threat Detection (33.14%) and Incident Response (21.51%), indicating that the main focus in the country's intelligence strategy is prevention and rapid response to potential manipulative practices. The results of the consistency evaluation (CR ≈ 0.0264) showed that the assessment between the criteria was consistent and accountable. Thus, the AHP method has been proven to be effective as a systematic and data-driven decision-making tool in the context of fiscal surveillance and state intelligence strategies in the face of transnational threats.